1998
DOI: 10.1038/bjc.1998.132
|View full text |Cite
|
Sign up to set email alerts
|

Spatial temporal patterns in childhood leukaemia: further evidence for an infectious origin

Abstract: Summary The EUROCLUS project included information on residence at diagnosis for 13 351 cases of childhood leukaemia diagnosed in the period 1980-89 in defined geographical regions in 17 countries. A formal algorithm permits identification of small census areas as containing case excesses. The present analysis examines spatial-temporal patterns of the cases (n = 970) within these clustered areas. The objectives were, first, to compare these results with those from an analysis conducted for UK data for the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Apart from the statistical significance, the best evidence that they are both genuine and aetiologically meaningful comes from further analyses that we have conducted of all small areas in which clusters were deemed to be present. These investigations revealed similar space-time interactions within the clusters (Alexander et al, 1998) to those that had been observed previously in data from the UK, 1966-83 (Alexander, 1992), and cannot readily be explained unless CL has an infectious origin. Further, cluster areas, when compared with control areas, were associated with demographic factors that have been the foundation for the remarkable series of studies by Kinlen and colleagues (Kinlen, 1995;Kinlen et al, 1995).…”
Section: Discussionsupporting
confidence: 82%
“…Apart from the statistical significance, the best evidence that they are both genuine and aetiologically meaningful comes from further analyses that we have conducted of all small areas in which clusters were deemed to be present. These investigations revealed similar space-time interactions within the clusters (Alexander et al, 1998) to those that had been observed previously in data from the UK, 1966-83 (Alexander, 1992), and cannot readily be explained unless CL has an infectious origin. Further, cluster areas, when compared with control areas, were associated with demographic factors that have been the foundation for the remarkable series of studies by Kinlen and colleagues (Kinlen, 1995;Kinlen et al, 1995).…”
Section: Discussionsupporting
confidence: 82%
“…Kinlen and colleagues have studied childhood leukaemia in a wide range of situations in which isolated populations were exposed to a large influx of outsiders or other sources of infectious agents (Kinlen et al, 1990(Kinlen et al, , 2002Kinlen and Stiller, 1993;Kinlen and John, 1994;Kinlen and Petridou, 1995;Kinlen, 1993Kinlen, , 1997Kinlen, , 2000aKinlen and Balkwill, 2001;Kinlen and Bramald, 2001). Other investigators have undertaken similar investigations in other situations and in other countries and obtained largely similar results (Langford, 1991;Roman et al, 1994;Dockerty et al, 1996;Petridou et al, 1996;Stiller and Boyle, 1996;Alexander et al, 1997Alexander et al, , 1998aDickinson and Parker, 1999;Fear et al, 1999;Birch et al, 2000;Koushik et al, 2001;Boutou et al, 2002;Dickinson et al, 2002aDickinson et al, , 2002bDickinson and Parker, 2002;Parslow et al, 2002). The effect is seen most strongly for ALL at ages 0 -4 and in the most rural areas (Kinlen et al, 1990(Kinlen et al, , 2002Stiller and Boyle, 1996;Alexander et al, 1997;Koushik et al, 2001;Kinlen and Balkwill, 2001;Kinlen and Bramald, 2001).…”
Section: Discussionmentioning
confidence: 59%
“…The results indicate statistically significant evidence of clustering of ALL in the childhood peak years as well as ALL at older age of onset, although the magnitude is small (Alexander et al, 1998). …”
Section: Discussionmentioning
confidence: 89%